A novel dorsal trimline approach for passive-dynamic ankle-foot orthoses - Sürmen, Hasan Kemal; Fetvacı, Mahmut Cüneyt; Arslan, Yunus Ziya; AKALAN, NAZİF EKİN (Assoc Mechanical Engineers Technicians Slovenia, Po Box 197-Iv, Ljubljana 61001, Slovenia, 2018)
An ankle-foot orthosis (AFO) is an externally applied assistive device that encompasses the lower leg, ankle, and foot of the human body. In the current one-piece passive-dynamic AFO design, the trimming process is performed from lateral and medial parts of the ankle to ensure desired rotational displacement (hereafter referred to as Design I). In most cases, stress concentrations occurring over the trimmed regions during walking can cause permanent damage to the AFO. In this study, to reduce the stress concentration and ensure a homogeneous stress distribution, a new trimming approach is presented, in which the trim zones were transferred from lateral and medial to dorsal (hereafter referred to as Design II). Finite element analyses of the Designs I and II models were carried out. Displacement and von Mises stress values for both models under the same loading and boundary conditions were obtained. Maximum displacement values were 8.51 mm and 9.05 mm for Design I and Design II, respectively. Maximum stress values were 15.19 MPa and 6.70 MPa for Design I and Design II, respectively. For the similar range of motion of ankle joint, the novel design produced less stress and more homogeneous stress distribution than the currently used design, thus indicating that Design II would be more resistant to plastic deformation than Design I.
Keywords: dorsal trimline; ankle-foot orthosis; finite element analysis; computer-aided design; 3D optical scanning; Mechanical-Properties; Gait Parameters; Alignment; Walking; Stroke; Polypropylene; Stiffness; Children; Balance